Comparative Techno-economic analysis of methanol production via carbon dioxide reforming of landfill gas using a highly active and stable Nickel-based catalyst. (1st May 2022) - Lee, Yeol-Lim; Lim, Dongjun; Lee, Boreum; Upadhyay, Mukesh; Brigljević, Boris; Roh, Hyun-Seog; Lim, Hankwon
Graphical abstract: Highlights: Nickel-based catalyst tolerates high gas hourly space velocity of 1, 620 L g −1 h −1 . Developed catalyst was compared with commercial carbon dioxide reforming catalyst. Reformer size is reduced by 23% due to the developed catalyst's high space velocity. Efficient heat utilization diminishes production cost by a factor of 2.5. Improved methanol production cost (36%) and energy efficiency (∼6%p) are reported. Abstract: The economic viability of a methanol production process through carbon dioxide reforming of landfill gas using a newly developed nickel-based catalyst was assessed. The development of the catalyst and techno-economic analysis of the designed process were targeted. The nickel-based catalyst showed a highly active and stable performance even at an extremely high gas hourly space velocity of 1, 620, 000 mL g −1 h −1 . The high activity of the catalyst was due to the abundant nickel active sites (metallic nickel particles) on its surface. Coke formation was suppressed by the small particle size of nickel and relatively high oxygen storage capacity, resulting in a stable catalytic performance. In the process simulation, the methanol production system based on the nickel-based catalyst (new process) leveraged its smaller reformer size and more efficient heat utilization compared to those of a previously reported system based on a rhodium-based catalyst (base process) because of its higher gas hourly space velocity. The process simulation was conducted based on the gas hourly space velocity of 312, 346 mL g −1 h −1 . The unit production costs of methanol were reduced from 184.0 ton −1 in the base process to 117.5 ton −1 in the new process. In addition, profitability analysis based on the global market price of methanol demonstrated that the new process exhibited a positive net present value, indicating economic feasibility, whereas the base process was not viable in the worst-case scenario (lowest market price of methanol).